Novel Concentric Hexagonal-Shaped RFID Tag Antenna With T-Shaped Stub Matching - Alibakhshikenari, Mohammad; Virdee, Bal S.; Althuwayb, Ayman A.; Xu, Kai Da; See, Chan Hwang; Khan, Salahuddin; Park, Ikmo; Falcone, Francisco; Limiti, Ernesto (IEEE Journal of Radio Frequency Identification, 2022)
This paper presents a unique concentric hexagonal-shaped ring antenna for radio frequency identification (RFID) tags. The rings are excited with a common microstrip feedline. The radiation characteristics of the antenna is improved by locating a horizontal a parasitic element in the vicinity of the hexagonal-shaped rings. The proposed antenna was used in the implementation of a $3× 1$ antenna array. The impedance match of the $3× 1$ RFID tag was enhanced by incorporating a T-shaped stub. The antenna is designed to operate at the UHF band from 800 MHz to 960 MHz. It was implemented on FR-4 substrate with dielectric constant and thickness of 4.3 and 1.6 mm, respectively. The size of the RFID tag antenna is $36× 10$ mm2. Its impedance was matched to Alien Higgs RFIC chip of impedance 10 & x2013; j $82.5~Ω $ at 895 MHz. Measured results show the proposed RFID tag antenna provides an impedance bandwidth, maximum gain and radiation efficiency of 160 MHz, 2 dBi, and 66.5& x0025;, respectively. With effective isotropic radiated power (EIRP) limited to 36 dBm to comply with FCC regulations for UHF band RFIDs it radiates in the broadside direction over a range of 9 m making it desirable for various applications including supply chain management, logistic control, and vehicle identification.
Keywords: Matchings; Microstrip feedline; Parasitic element; Radiation characteristics; Radiofrequencies; Radiofrequency identification; Radiofrequency identification tags; Ring antennas; Tag antenna; UHF band; Radiofrequency identification